Electrochemical energy storage electrode with high loading capacity and application thereof

By using Pb10-xCux(PO4)6O material to prepare electrodes, the problem of limited load of active materials in existing electrochemical energy storage devices is solved, and electrochemical energy storage electrodes with high energy density and high power density are realized, suitable for multiple Electrochemical energy storage device.

CN119446793AInactive Publication Date: 2025-02-14SOUTHEAST UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310977098.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to the poor conductivity of active materials, the existing electrochemical energy storage devices have limited loads of active materials on their electrodes, making it difficult to improve the energy density and power density of energy storage devices.

Method used

Using Pb10-xCux(PO4)6O as the electrode active material, materials with different morphology are prepared by ball milling or three-step solid phase reaction, and mixed with binder and conductive agent to make a slurry, and pressed into an electrode sheet to increase the load capacity. .

Benefits of technology

The electrochemical energy storage electrode with high load capacity is achieved, providing high energy density and high power density, suitable for supercapacitors and secondary ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446793A_ABST
    Figure CN119446793A_ABST
Patent Text Reader

Abstract

The invention discloses an electrochemical energy storage electrode with high loading capacity and application thereof, the active material of the electrode is Pb < 10-x > Cux (PO4) 6O, and 0.9 lt; xlt; 1.1. The Pb < 10-x > Cux (PO4) 6O can have different morphological characteristics. The preparation process of the electrode comprises the following steps: (1) preparing Pb10-xCux (PO4) 6O materials with different morphologies through ball milling or three-step solid-phase reaction; and (2) grinding Pb10-xCux (PO4) 6O, directly and uniformly pressing the Pb10-xCux (PO4) 6O into an electrode plate, or mixing the Pb10-xCux (PO4) 6O with a binder and a conductive agent to obtain slurry, uniformly coating the surface of a current collector with the slurry to form a Pb10-xCux (PO4) 6O layer, and pressing the Pb10-xCux (PO4) 6O layer into an electrode plate to obtain the energy storage electrode. The energy storage electrode has the characteristics of low cost, high energy and high power, and is expected to be used for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an energy storage electrode and application thereof, and in particular to an electrochemical energy storage electrode with high loading capacity and application thereof. Background Art

[0002] Electrochemical energy storage devices, especially supercapacitors, are efficient energy storage devices with advantages such as high capacitance, ultra-high power density, excellent reversibility, high instantaneous power, and fast charging and discharging.

[0003] Currently, the use of electrode materials (such as activated carbon, metal materials and transition metal oxides) as electrochemical energy storage electrodes is a feasible method for developing and manufacturing efficient, reliable and low-cost energy storage devices. However, due to the poor conductivity of the active materials in existing electrochemical energy storage devices, the active material loading capacity of their electrodes is limited, making it difficult to improve the energy density and power density of energy storage devices. For example, supercapacitors are expected to be used as the main power source for equipment or systems. Their development towards higher power density, maintenance-free and long life can further expand their market share in certain special fields. However, they face technical difficulties in the urgent need to improve their energy density and power density. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide an electrochemical energy storage electrode with improved energy density and power density and high loading capacity;

[0005] The second object of the present invention is to provide the application of the electrochemical energy storage electrode with high loading capacity.

[0006] Technical solution: The electrochemical energy storage electrode with high loading capacity of the present invention, the electrode active material is Pb 10-x Cu x (PO4)6O, of which 0.9 <x<1.1。

[0007] Among them, Pb 10-x Cu x The thickness of the electrode prepared from (PO4)6O active material is 50 μm to 1 cm; when the electrode includes a current collector, the thickness refers to the thickness of the current collector and the active material layer; when the electrode is directly pressed into an electrode sheet by the active material, the thickness refers to the thickness of the pure active material layer.

[0008] Wherein, the electrode is formed by 10-x Cu x The (PO4)6O active material is pressed into electrode sheets.

[0009] Wherein, the electrode is formed by 10-x Cu x(PO4)6O active material is mixed with a binder and a conductive agent to obtain a slurry, which is coated on the surface of a current collector and pressed into an electrode sheet to prepare it.

[0010] Among them, Pb 10-x Cu x (PO4)6O active material is in the form of bulk powder or lamellar powder.

[0011] Among them, Pb 10-x Cu x (PO4)6O active material is prepared through the following steps:

[0012] Mix Cu powder, P powder, PbO and Pb(SO4) by grinding, then mix the mixture with water and zirconia balls and carry out ball milling to obtain Pb10-xCux(PO4)6O lamellar powder; or,

[0013] Mix PbO and Pb(SO4) and then calcine to obtain sample A, mix Cu powder and P powder and then calcine to obtain sample B, and then grind and mix sample A and sample B and calcine to obtain Pb 10-x Cu x (PO4)6O bulk powder.

[0014] Specifically, the ball milling reaction is as follows: Weigh and mix Cu, P, PbO and Pb(SO4) powders according to the elemental ratio of Pb 10-x Cu x (PO4)6O (0.9 < x < 1.1), mix the mixture with water and zirconia balls in a mass ratio of 1:1:5, and use a ball mill to ball mill for 48 hours to obtain Pb 10-x Cu x (PO4)6O lamellar material; the molar mass ratio of the Cu powder to the P powder is 10:1 - 1:5, and the molar mass ratio of PbO to Pb(SO4) is 1:1.

[0015] The three-step solid-phase reaction is as follows. The first step: Uniformly mix PbO and Pb(SO4) powders in a ratio of 1:1 in a ceramic crucible, conduct a sealed tube treatment in an air atmosphere, place it in a tube furnace, and calcine at 725 °C for 24 hours; the second step: Uniformly mix Cu powder and P powder according to different ratios, conduct a sealed tube treatment, and then place it in a tube furnace and calcine at 550 °C for 48 hours; the third step: Grind the systems obtained in the first step and the second step, uniformly mix them, conduct a sealed tube treatment, and place it in a tube furnace and calcine at 925 °C for 5 - 20 hours to obtain Pb 10-x Cu x (PO4)6O bulk.

[0016] Among them, in the slurry, Pb 10-x Cu xThe mass proportions of (PO4)6O active material, binder and conductive agent are 90-100%, 0-6% and 0-4% respectively.

[0017] Among them, the binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, hydroxymethyl cellulose or polyvinyl alcohol; the conductive agent is at least one of acetylene black, Ketjen black, activated carbon, graphene, carbon nanotubes or carbon fibers; the current collector is at least one of aluminum foil, copper foil, titanium foil, nickel foil or carbon paper.

[0018] Application of the above-mentioned electrochemical energy storage electrode with high loading capacity in an electrochemical energy storage device.

[0019] Specifically, applications in supercapacitors and secondary ion batteries.

[0020] Specifically, the capacitor is one of a symmetric capacitor and an asymmetric capacitor, wherein the electrodes of the symmetric supercapacitor are the same, while the electrodes of the asymmetric supercapacitor are different; more preferably, it is an asymmetric supercapacitor, using the electrode of the present invention as the positive electrode and a conventional carbon material as the negative electrode.

[0021] The secondary ion battery is one or more of an organic / aqueous lithium ion battery, an organic / aqueous sodium ion battery and an organic / aqueous zinc ion battery.

[0022] Invention principle: Using Pb 10-x Cu x The electrochemical energy storage electrode prepared by (PO4)6O material has the characteristics of ultra-high active material loading, which can provide high energy density and high power density. Firstly, this is due to the fact that Pb 10-x Cu x (PO4)6O has a large surface area and can provide more active sites; secondly, Pb 10-x Cu x (PO4)6O has an extremely low resistivity, which can meet the preparation requirements of high-load energy storage electrodes with larger thickness, less conductive agent or even no conductive agent. It is precisely because of this low resistance advantage and the matching electrode preparation process that a thicker and more loaded electrode slurry can be obtained, thereby improving the energy density and power density of electrochemical energy storage devices.

[0023] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0024] (1) The active material of the electrochemical energy storage electrode with high loading capacity of the present invention is Pb 10-x Cu x(PO4)6O(0.9 < x < 1.1), due to its extremely large specific surface area and extremely low resistivity, enables high loading on the electrode, and the electrochemical energy storage device using this electrode exhibits extremely high energy density and power density. (2) The Pb 10-x Cu x (PO4)6O active material can be prepared with different morphologies through ball milling or a three-step solid-state reaction. When preparing the electrode, the Pb 10-x Cu x (PO4)6O material can be directly and uniformly pressed to obtain an electrode sheet, or the Pb 10-x Cu x (PO4)6O is ground and then mixed with a binder and a conductive agent to prepare a slurry, which is coated on the surface of the current collector to form a Pb 10-x Cu x (PO4)6O layer, and then pressed into an electrode sheet. (3) The electrochemical energy storage electrode of the present invention with a high loading amount can be applied to electrodes of supercapacitors and secondary ion batteries. For supercapacitors, such as symmetric supercapacitors and asymmetric supercapacitors; for secondary ion batteries, it can be used for electrodes of lithium-ion batteries, sodium-ion batteries, and zinc-ion batteries. (4) The electrochemical energy storage electrode of the present invention with a high loading amount can be applied to organic-based ionic solutions or aqueous ionic solutions, having the diversity and stability for various scenario applications and providing a good cycle life. (5) The synthesis method of this material and the electrode preparation method have the characteristics of simple operation and low cost, meeting industrial scale-up experiments and being convenient for industrial application. Description of the Drawings

[0025] Figure 1 is the electron microscope image of the Pb 10-x Cu x (PO4)6O material prepared in Example 1 and Example 2;

[0026] Figure 2 is the elemental scanning image of the Pb 10-x Cu x (PO4)6O sheet-like material prepared in Example 2;

[0027] Figure 3 is the X-ray diffraction pattern of the Pb 10-x Cu x (PO4)6O material prepared in Example 1;

[0028] Figure 4 is the chemical structure diagram of the Pb 10-x Cu x (PO4)6O material;

[0029] Figure 5 is in Example 1 based on Pb 10-x Cux Performance diagram of supercapacitor with (PO4)6O electrode;

[0030] Figure 6 In Example 2, based on Pb 10-x Cu x Performance diagram of supercapacitor with (PO4)6O electrode;

[0031] Figure 7 In Example 3, based on Pb 10-x Cu x Performance diagram of supercapacitor with (PO4)6O electrode;

[0032] Figure 8 In Example 4, based on Pb 10-x Cu x Performance diagram of supercapacitor with (PO4)6O electrode;

[0033] Fig. 9 In Example 5, based on Pb 10-x Cu x Performance diagram of supercapacitor with (PO4)6O electrode;

[0034] Fig.10 In Example 6, based on Pb 10-x Cu x Performance diagram of supercapacitor with (PO4)6O electrode;

[0035] Fig.11 In Example 7, based on Pb 10-x Cu x Supercapacitor performance diagram of (PO4)6O electrode. DETAILED DESCRIPTION

[0036] The present invention is described in further detail below.

[0037] Example 1

[0038] Weigh 2.23g PbO and 3.03g Pb(SO4) respectively, mix them thoroughly, seal the tube, and place it in a tube furnace. After calcining at 725℃ for 24 hours, sample A is obtained; weigh 1.89g Cu and 0.31g P powder respectively, mix them evenly, put them into a tube furnace, and calcine at 550℃ for 48 hours to obtain sample B; weigh 0.53g sample A and 0.22g sample B respectively, grind and mix them thoroughly, place them in a tube furnace, and calcine at 925℃ for 5 hours to obtain Pb 10-x Cu x (PO4)6O material.

[0039] like Figure 1 As shown in the left figure, the obtained Pb 10-xCu x (PO4)6O material is a bulk powder, which has the characteristics of extremely low resistivity. 10-x Cu x The X-ray diffraction curve of (PO4)6O material is shown in Figure 3 shown.

[0040] The obtained Pb 10-x Cu x After the (PO4)6O bulk powder material is fully ground and dispersed, it is mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of Pb 10-x Cu x (PO4)6O: polyvinylidene fluoride: conductive carbon black = 95:3:2 weighed, and then added N-methylpyrrolidone and mixed thoroughly to form an electrode slurry. The viscous electrode slurry was coated on the nickel foil current collector to form a Pb 10-x Cu x The (PO4)6O layer is dried and pressed to obtain an electrochemical energy storage electrode, wherein the thickness of the coated slurry is 50 μm.

[0041] The obtained electrode was cut into a 1 cm diameter disc as a supercapacitor electrode, matched with a graphite electrode with sufficient loading as a counter electrode, and assembled into an asymmetric button supercapacitor for performance testing. Among them, the diaphragm is a cellulose-based diaphragm and the electrolyte is a 3M KOH solution. The test results are as follows Figure 5 As shown, when the power density is 100W / kg, the energy density of the supercapacitor is 35.2Wh / kg; when the power density is increased to 20000W / kg, the energy density reaches 30.5Wh / kg.

[0042] Example 2

[0043] Cu, P, PbO and Pb(SO4) powders were weighed in a mass ratio of 2.0:0.3:2.2:3.0, and after being fully ground and mixed, the mixture was mixed with water and zirconia balls in a mass ratio of 1:1:5, and ball milled for 48 hours to obtain Pb 10-x Cu x (PO4)6O flake powder, such as Figure 1 The element scanning diagram is shown in the middle right figure. Figure 2 As shown. 10-x Cu x The chemical structure of (PO4)6O material is shown in the figure Figure 4 shown.

[0044] The obtained Pb 10-x Cu xAfter the (PO4)6O flake powder material is fully and evenly ground, an appropriate amount is taken and pressed into an electrode sheet with dense particles using a tablet press, wherein the pressed electrode has a thickness of 1 cm.

[0045] The obtained electrode sheet was used as a supercapacitor electrode, and a graphite electrode with sufficient loading was matched as a counter electrode. An electrolytic cell was used to assemble an asymmetric supercapacitor for performance testing. The electrolyte used was 3M KOH solution. The test results are shown in Figure 2. Figure 6 As shown, when the power density is 100W / kg, the energy density of the supercapacitor is 33.7Wh / kg; when the power density is increased to 20000W / kg, the energy density reaches 28.7Wh / kg.

[0046] Example 3

[0047] The Pb obtained in Example 1 10-x Cu x After the (PO4)6O bulk powder material is fully ground and dispersed, it is mixed with polyvinyl alcohol and Ketjen black in a mass ratio of Pb 10-x Cu x (PO4)6O: polyvinyl alcohol: ketjen black = 98:1.4:0.6, and then add N-methylpyrrolidone and mix thoroughly to form an electrode slurry. Apply the viscous electrode slurry on the nickel foil current collector to form Pb 10- x Cu x The (PO4)6O layer is dried and pressed to obtain an electrochemical energy storage electrode, wherein the thickness of the coated slurry is 2 mm.

[0048] The obtained electrode was cut into a 1 cm diameter disc as a supercapacitor electrode, matched with a graphite electrode with sufficient loading as a counter electrode, and assembled into an asymmetric button supercapacitor for performance testing. Among them, the diaphragm is a cellulose-based diaphragm and the electrolyte is a 3M KOH solution. The test results are as follows Figure 7 As shown, when the power density is 100W / kg, the energy density of the supercapacitor is 34.5Wh / kg; when the power density is increased to 20000W / kg, the energy density reaches 29.1Wh / kg.

[0049] Example 4

[0050] The Pb obtained in Example 1 10-x Cu x After the (PO4)6O bulk powder material is fully ground and dispersed, it is mixed with polytetrafluoroethylene aqueous solution and carbon nanotubes at a mass ratio of Pb 10-x Cu x(PO4)6O: polytetrafluoroethylene: carbon nanotubes = 98:1:1 weighed, fully mixed to form an electrode slurry. The electrode slurry was pressed onto an aluminum foil current collector to form a Pb 10-x Cu x (PO4)6O layer, and after drying, an electrochemical energy storage electrode is obtained, wherein the pressed slurry thickness is 1 cm.

[0051] The obtained electrode sheet was used as a supercapacitor electrode, and a graphite electrode with sufficient loading was matched as a counter electrode. An electrolytic cell was used to assemble an asymmetric supercapacitor for performance testing. The electrolyte used was 3M KOH solution. The test results are shown in Figure 2. Figure 8 As shown, when the power density is 100W / kg, the energy density of the supercapacitor is 34.7Wh / kg; when the power density is increased to 20000W / kg, the energy density reaches 29.0Wh / kg.

[0052] Example 5

[0053] The Pb obtained in Example 2 10-x Cu x After the (PO4)6O lamellar powder material is fully and evenly ground, an appropriate amount is taken and pressed into an electrode sheet with dense particles using a tablet press, wherein the pressed electrode has a thickness of 500 μm.

[0054] The obtained electrode sheet was used as a supercapacitor electrode, and a graphite electrode with sufficient loading was matched as a counter electrode. An electrolytic cell was used to assemble an asymmetric supercapacitor for performance testing. The electrolyte used was 3M KOH solution. The test results are shown in Figure 2. Fig. 9 As shown, when the power density is 100W / kg, the energy density of the supercapacitor is 35.0Wh / kg; when the power density is increased to 20000W / kg, the energy density reaches 30.1Wh / kg.

[0055] Example 6

[0056] The Pb obtained in Example 1 10-x Cu x After the (PO4)6O bulk powder material is fully ground and dispersed, it is mixed with polyvinyl alcohol and activated carbon in a mass ratio of Pb 10-x Cu x (PO4)6O:polyvinyl alcohol:activated carbon=96:3.5:2.5, weigh and add N-methylpyrrolidone to mix thoroughly to form electrode slurry. Apply the viscous electrode slurry on the aluminum foil current collector to form Pb 10- x Cu x The (PO4)6O layer is dried and pressed to obtain an electrochemical energy storage electrode, wherein the thickness of the coated slurry is 1 mm.

[0057] The obtained electrode was cut into a 1 cm diameter disc as a supercapacitor electrode, matched with a graphite electrode with sufficient loading as a counter electrode, and assembled into an asymmetric button supercapacitor for performance testing. Among them, the diaphragm is a cellulose-based diaphragm and the electrolyte is a 3M KOH solution. The test results are as follows Fig.10 As shown, when the power density is 100W / kg, the energy density of the supercapacitor is 35.5Wh / kg; when the power density is increased to 20000W / kg, the energy density reaches 30.2Wh / kg.

[0058] Example 7

[0059] The Pb obtained in Example 1 10-x Cu x After the (PO4)6O bulk powder material is fully ground and dispersed, it is mixed with polyvinylidene fluoride and carbon fiber in a mass ratio of Pb 10-x Cu x (PO4)6O: polyvinylidene fluoride: carbon fiber = = 98:1.4:0.6 weighed, and then added N-methylpyrrolidone and mixed thoroughly to form an electrode slurry. The viscous electrode slurry was coated on the nickel foil current collector to form a Pb 10-x Cu x The (PO4)6O layer is dried and pressed to obtain an electrochemical energy storage electrode, wherein the thickness of the coated slurry is 800 μm.

[0060] The obtained electrode was cut into 1 cm diameter discs as supercapacitor electrodes, and two of the electrodes were used to assemble a symmetrical button-type supercapacitor for performance testing. The diaphragm used was a cellulose-based diaphragm, and the electrolyte used was a 3M KOH solution. The test results are shown in Figure 2. Fig.11 As shown, when the power density is 100W / kg, the energy density of the supercapacitor is 89.7Wh / kg; when the power density is increased to 20000W / kg, the energy density reaches 78.5Wh / kg.

Claims

1. An electrochemical energy storage electrode with a high loading capacity, characterized in that: The electrode active material is Pb 10-x Cu x (PO4)6O, of which 0.9 <x<1.1。 2. The electrochemical energy storage electrode with high loading according to claim 1, characterized in that: Pb 10-x Cu x The thickness of the electrode prepared from (PO4)6O active material is 50 μm to 1 cm.

3. The electrochemical energy storage electrode with high loading according to claim 1, characterized in that: The electrode is made by 10-x Cu x The (PO4)6O active material is pressed into electrode sheets.

4. The electrochemical energy storage electrode with high loading according to claim 1, characterized in that: The electrode is made by 10-x Cu x The (PO4)6O active material is mixed with a binder and a conductive agent to obtain a slurry, which is then coated on the surface of a current collector and pressed into an electrode sheet.

5. The electrochemical energy storage electrode with high loading according to claim 1, characterized in that: Pb 10-x Cu x The (PO4)6O active material is a bulk powder or a flaky powder.

6. The electrochemical energy storage electrode with high loading according to claim 1, characterized in that: Pb 10-x Cu x The (PO4)6O active material was prepared by the following steps: Cu powder, P powder, PbO and Pb(SO4) were ground and mixed, and then the mixture was mixed with water and zirconium oxide balls and ball milled to obtain Pb 10-x Cu x (PO4)6O lamellar powder; or PbO and Pb(SO4) were mixed and calcined to obtain sample A, Cu powder and P powder were mixed and calcined to obtain sample B, and then sample A and sample B were ground and mixed and calcined to obtain Pb 10-x Cu x (PO4)6O bulk powder.

7. The electrochemical energy storage electrode with high loading according to claim 4, characterized in that: The Pb in the slurry 10-x Cu x The mass proportions of (PO4)6O active material, binder and conductive agent are 90-100%, 0-6% and 0-4% respectively.

8. The electrochemical energy storage electrode with high loading according to claim 4, characterized in that: The binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, hydroxymethyl cellulose or polyvinyl alcohol; the conductive agent is at least one of acetylene black, Ketjen black, activated carbon, graphene, carbon nanotubes or carbon fibers; the current collector is at least one of aluminum foil, copper foil, titanium foil, nickel foil or carbon paper.

9. Use of the electrochemical energy storage electrode with high loading capacity as claimed in claim 1 in an electrochemical energy storage device.

10. Use of the electrochemical energy storage electrode with high loading capacity in an electrochemical energy storage device according to claim 9, characterized in that: Applications in supercapacitors and secondary ion batteries.

Citation Information

Patent Citations

  • Room temperature and environment pressure superconducting ceramic compound and production method thereof

    CN117837303A

  • Room-temperature and ambient-pressure superconducting ceramic and methods for producing the same

    US20240355500A1

  • Room-temperature and ambient-pressure superconducting ceramic and methods for producing the same

    US20250250170A1

  • Room temperature and normal pressure superconducting ceramic compound, and method for manufacturing same

    WO2023027536A1

  • Room-temperature and atmospheric-pressure superconducting ceramic compound and preparation method therefor

    WO2023027537A1